Cueva de los Torrejones revisited. New insights on the paleoecology of inland Iberia during the Late Pleistocene. (1st February 2021) - Sala, Nohemi; Pablos, Adrián; Rodríguez-Hidalgo, Antonio; Arriolabengoa, Martin; Alcaraz-Castaño, Manuel; Cubas, Miriam; Posth, Cosimo; Nägele, Kathrin; Pantoja-Pérez, Ana; Arlegi, Mikel; Rodríguez-Almagro, Manuel; Conde-Valverde, Mercedes; et al.
Abstract: The interior of the Iberian Peninsula has orographic conditions that make this territory especially vulnerable to Quaternary climate oscillations and which actually could have made it decisive for Paleolithic human populations at critical points. For this reason, the information provided by paleontological sites is important for reconstructing climatic and environmental conditions during the Late Pleistocene and understanding how they influenced the species that inhabited them, including humans. Nevertheless, the archaeo-paleontological record is scarce in central Iberia for the Late Pleistocene. A central Iberian site that is key to addressing this issue is Cueva de los Torrejones, which was discovered and excavated during the nineties. Clues indicating the presence of Neandertal populations near the cave site were announced during prior field excavations, including Neandertal remains, Middle Paleolithic artifacts, and evidence of anthropic exploitation of faunal resources at the site. Here we report the new results from the recent excavations and research, including detailed studies on stratigraphy, micromorphology, macro and microvertebrate paleontology, physical and molecular anthropology, taphonomy and zooarchaeology, and analysis of lithic and pottery remains. Our research has led to the detection of three Prehistoric chronologies recorded at the site. The oldest episode corresponds to between MIS 5 and MIS 4 in which the cave was used by carnivores. The second episode is represented by a faunal association dated to 30.0 ka cal BP and is indicative of cooler and more arid environmental conditions and, therefore, compatible with the worsening climate detected previously for MIS 3 in this area. The last episode corresponds to the Chalcolithic, directly dated to ∼5000 cal BP in which humans used the cavity for funerary purposes. The DNA analysis of the human remain was assigned to mtDNA haplogroup K, which was originated in the Near East and reached western Europe through the Neolithic expansion. Human occupation during the Paleolithic has been ruled out, including Paleolithic human remains and any kind of anthropic intervention on the Hermann's tortoise and leopard as was previously proposed at the site. Highlights: Cueva de los Torrejones is located in Central Iberia. Three Prehistoric chronologies have been detected: MIS4/5, MIS3 and Chalcolithic. Paleoecological information on the Middle-Upper Paleolithic transition is provided. We document a climatic deterioration during the mid-MIS 3 in Central Iberia. Paleolithic human remains and cut marks on tortoise and leopard have been ruled out.